About ból and symptomy… Lexical analysis in Polish as a foreign language classes for German paramedics - LISEK, GRZEGORZ (Glottodidactica, 2021)
This paper focuses on the lexical side of the emergency communication of German paramedics who are learning Polish as a foreign language for professional purposes. The aim of the study is to find out which lexical units arise during language courses and how often. To what extent can the acquired vocabulary be used to develop dedicated programmes for foreign language acquisition in medical emergency communication? The analysis shows that the vocabulary collected here depends on the subject, such as ból (pain) or leki (medicines). According to the participants, symptomy (symptoms) and duszności (shortness of breath) are also part of the common vocabulary. Emergency medical communication can be carried out with the question pronouns kiedy (when) and gdzie (where). Among the most frequently repeated lexical units of vital parameters during patient transfer are saturacja (oxygen saturation) and puls (pulse). The vocabulary collected here should help in preparing a description of the competences which should form part of a language course for professional purposes.